The effects of interest rates and gross national saving (GNS) on the profitability of local commercial bank in Malaysia / Murizah Mohamad Safari (Faculty of Business and Management, 2006)
In this project paper, the aim of this research is to identify which independent variables namely interest rate and gross national saving (GNS) are affecting the profitability of local commercial bank in Malaysia. This research involves ten (10) local commercial banks in Malaysia. The sample period is from year 2001 to year 2005. The balance sheet and income statement are used to measure the profitability ratio of the each bank. In this study, the effect of interest rate and gross national saving on the profitability of local commercial bank in Malaysia is ambiguous. In the empirical section of the paper the researcher test the profitability ratio hypothesis using balance sheet and income statement local commercial bank data. Multiple regressions method was conducted on the equations in order to test the each relationship of the variables. From the result, we find that, indeed, economic factors tend to increase or decrease the profitability of local commercial bank.